2020
DOI: 10.3390/plants9030306
|View full text |Cite
|
Sign up to set email alerts
|

The First Plastid Genome of the Holoparasitic Genus Prosopanche (Hydnoraceae)

Abstract: Plastomes of parasitic and mycoheterotrophic plants show different degrees of reduction depending on the plants’ level of heterotrophy and host dependence in comparison to photoautotrophic sister species, and the amount of time since heterotrophic dependence was established. In all but the most recent heterotrophic lineages, this reduction involves substantial decrease in genome size and gene content and sometimes alterations of genome structure. Here, we present the first plastid genome of the holoparasitic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 53 publications
(101 reference statements)
0
36
0
Order By: Relevance
“…We obtained four chloroplast genes (matK, rbcl, trnL and trnL-trnF) and one nuclear marker (ITS) for 247 species of perianth-bearing Piperales (~49% of the total species diversity 130 ) and six outgroups from perianth-less Piperales. We could not include the two genera Hydnora and Prosopanche (Hydnoraceae) because available genetic data do not overlap those of perianth-bearing Piperales 126,128,131,132 . We applied the same analytical procedure that we did for Papilionidae.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained four chloroplast genes (matK, rbcl, trnL and trnL-trnF) and one nuclear marker (ITS) for 247 species of perianth-bearing Piperales (~49% of the total species diversity 130 ) and six outgroups from perianth-less Piperales. We could not include the two genera Hydnora and Prosopanche (Hydnoraceae) because available genetic data do not overlap those of perianth-bearing Piperales 126,128,131,132 . We applied the same analytical procedure that we did for Papilionidae.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study grouped the Hydnoraceae family as a sister group to the Winteraceae family ( Drimys granadensis ) because of the long branching problem [ 45 ]. Another study indicated that the Hydnoraceae family formed a monophyletic clade with a low bootstrap support value of 13%, which cannot justify the grouping of Hydnoraceae [ 3 ]. To date, only H. visseri and H. abyssinica complete genomes have been studied in this genus (5, Mkala et al in press).…”
Section: Botanical Features and Taxonomymentioning
confidence: 99%
“…They are native and distributed in arid and semi-arid parts of Africa and Asia. This family contains two genera; Hydnora and Prosopanche , named among the oldest parasitic lineages [ 1 , 2 , 3 ]. Prosopanche is naturally found in Central America and South America, whereas Hydnora is indigenous to Africa, Madagascar, and the Arabian Peninsula [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plastome of such plant species provides an excellent tool to study the loss of organelle genetic material to the nucleus while they shift from the autotrophic to the heterotrophic mode. Jost et al [8] sequenced the plastome of a holoparasitic plant species, Prosopanche americana, which has only 24 housekeeping genes and has lost the inverted repeats (IR) that are thought to stabilize the genome. The genetic machinery of P. americana shows an incredibly high degree of bias towards "AT"-rich codons, with >90% of the plastome sequence containing "A" and "T" nucleotides.…”
Section: Characteristics and Rearrangements Of Plant Organelle Genomementioning
confidence: 99%